Binational Universities: Platforms for Cross-Border Academic and Economic Development - Lane, Jason; Schueller, Jessica (International Higher Education, 2025)
Binational universities are a form of transnational education formed through bilateral agreements between governments, combining the educational systems of two countries. Unlike international branch campuses, they are entirely new institutions aimed at promoting cross-border collaboration, academic innovation, research, and economic development. Despite challenges related to governance and funding, binational universities are a promising model for fostering international cooperation and addressing global issues through collaborative efforts.